Paranoid styles and innumeracy: implications of a conspiracy mindset on Europeans' misperceptions about immigrants. (27th March 2022) - Martini, Sergio; Guidi, Mattia; Olmastroni, Francesco; Basile, Linda; Borri, Rossella; Isernia, Pierangelo
Abstract: Innumeracy, that is, the inability to deal with numbers and provide correct estimates about political issues, is reported to be widespread among the public. Yet, despite the recognition that a conspiracy mindset is an increasingly common phenomenon in Western democracies, this has not been considered as a potential correlate of innumeracy. Using data from an online sample of respondents across 10 European countries, we show that those with a higher propensity to hold a conspiracy worldview tend to overestimate the actual share of the immigrant population living in their own country. This association holds true when accounting for country heterogeneity and other cognitive, affective and socio-demographic factors. Employing a comparative design and refined measurements, the article contributes to our understanding of how a conspiracy mentality may influence perceptions of relevant political facts, questioning basic processes of democratic accountability.